Clinical Outcomes and Gingival Blood Flowmetry of Two Types of Subepithelial Connective Tissue Graft for Root Coverage in Multiple Gingival Recessions: A Preliminary Study - Ragghianti-Zangrando, Mariana Schutzer; Margarido Brondino, Nair Cristina [UNESP]; Damante, Carla Andreotti; Balderrama, Isis de Fatima; Veronesi, Giovana Fuzeto; Cardoso, Matheus Volz; Passanezi Sant'Ana, Adriana Campos (Quintessence Publishing Co Inc, 2021)
This randomized split-mouth preliminary clinical trial aimed to evaluate periodontal parameters and gingival blood flowmetry, comparing sites that received subepithelial connective tissue graft from the palate after deepithelialization (DE) or obtained with parallel incision (PI). Periodontal parameters were evaluated at baseline and 6 months postoperative. Gingival blood flows were analyzed by laser Doppler flowmetry (LDF) at baseline and 2, 7, and 14 days postoperative. Statistical and LDF analyses were performed with R version 3.5.1 and MATLAB software, and clinical parameters through ANOVA and Wilcoxon signed-rank tests. LDF showed superior decrease in power spectral density (PSD) for DE after 2 days. After 7 days, PSD returned to initial values only for PI, and DE had not returned to the initial values by day 14. Despite major initial revascularization challenges for DE sites, both grafts promoted satisfactory root coverage in the treatment of multiple gingival recessions.